Identification and association of recurrent ALOXE3 mutation with non‐bullous congenital ichthyosiform erythroderma in two ethnically distinct Pakistani families. (18th July 2018) - Rahman, Simeen Ber; Mir, Asif; Ahmad, Nafees; Haider, Syed Husnain; Malik, Salman Akbar; Nasir, Muhammad
Abstract : Non‐bullous congenital ichthyosiform erythroderma (NCIE) is characterized by skin scaling with erythema. In this study, two Pakistani families with NCIE are genetically characterized through Whole Exome and Sanger sequencing to identify molecular basis of the disease. We identified a nonsense homozygous c.2026C>T mutation of ALOXE3, causing premature termination of the eLOX3 protein (p.Q676X). In silico studies predicted impaired enzymatic activity of the premature truncated eLOX3, leading to abnormal synthesis of specific hepoxilin derivatives, essential for epidermal barrier formation. It is the first ever study reporting homozygotes of p.Q676X mutation in ethnically distinct two Pakistani families; otherwise, heterozygotes of the said mutation have been reported in South Asian population only. Hence, mutation seems to be region‐specific and may be useful for molecular diagnosis of NCIE. Moreover, our findings should help in genetic counseling and career screening.